2013
DOI: 10.4067/s0301-732x2013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zona pellucida removal on early development of in vitro produced bovine embryos

Abstract: SUMMARYDuring early embryo development the zona pellucida acts as a barrier against polyspermia and guarantees communication between blastomeres before and during compaction. However, the development of new technologies of embryo production such as "Handmade Cloning" demands removal of this membrane. The aim of this study was to determine the effect of zona pellucida removal on in vitro bovine embryo development. First, the consequences of zona pellucida removal was assessed by comparing the percentage of firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…According to obtained results, hatching rate was significantly lower in the IVF-derived embryos than in the in vivo control. Although a correct hatching process occurs normally in a good quality blastocyst, it is shown that in vitro conditions cause zona hardening, and disturb the hatching ability of a produced embryo(39). Furthermore, the success of in vitro hatching is dependent on a sufficiently high number of embryonic cells(40) as well as trophectodermal lysins (41).…”
Section: Discussionmentioning
confidence: 99%
“…According to obtained results, hatching rate was significantly lower in the IVF-derived embryos than in the in vivo control. Although a correct hatching process occurs normally in a good quality blastocyst, it is shown that in vitro conditions cause zona hardening, and disturb the hatching ability of a produced embryo(39). Furthermore, the success of in vitro hatching is dependent on a sufficiently high number of embryonic cells(40) as well as trophectodermal lysins (41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the cell cycle length of the PA embryos appeared to be longer than that of the IVF embryos [23]. PA embryos produced by ethanol activation (a method similar to that of the present study) have few cells [24], and the apoptotic indexes of PA embryos are higher than that of IVF embryos [25]. (2) It is possible that the PA embryos had only a small amount of the enzyme that melts the zona pellucida.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have established that bovine zona removal is most effectively achieved using 0.2% proteinase K for 5 min and that this process exhibited low toxicity [19]. In contrast, treatment with 0.5% proteinase K took approximately 6.8 min to completely remove the ZP in mouse embryos suggesting that it is not as efficient in mice.…”
Section: Discussionmentioning
confidence: 98%